Pemanfaatan asap cair serbuk kayu sebagai koagulan bokar - Agus Wijaya, Eli Yulita, Basuni Hamzah, (Balai Riset dan Standardisasi Industri Palembang, 2011)
Industrial wastes of rubber wood and gelam wood processing have not been maximally utilized and frequently create environment pollution. Liquid smoke from industrial waste of sawdust through pyrolysis has potential as coagulant for rubber latex. This research objective was to study the utilization of liquid smoke from pyrolysis results of rubber wood (Hevea brasiliensis M) and gelam wood (Melaleuca leucadendron L) as coagulants of rubber processed material. This study used Factorial Completely Randomized Design with two treatment factors consisting of liquid wastes of rubber sawdust (0%, 5%, 10% and 15%) and gelam sawdust (0%, 5%, 10% and 15%). The observed parameters were dryrubber content (%) and thickness of air dried rubber sheet (mm). The results showed that addition of 10% concentration liquid smoke of rubber wood (K10G10) can increase the dry rubber content and produced thin rubber processed material which were shown by the highest dry rubber content of 99.79% and the least thickness of 2.03 mm.Keywords : Rubber wood, gelam wood, air dried sheet AbstrakLimbah industri pengolahan kayu karet dan kayu gelam belum dimanfaatkan secara maksimal dan sering menimbulkan pencemaran lingkungan. Asap cair limbah serbuk kayu industri hasil pirolisis mempunyai potensi sebagai bahan pembeku lateks karet. Penelitian ini bertujuan untuk mengetahui pemanfaatan asap cair hasil pirolisis serbuk kayu karet (Hevea brasiliensis M) dan kayu gelam (Melaleuca leucadendron L) sebagai koagulan bokar. Penelitian ini menggunakan rancangan acak lengkap faktorial dengan dua faktor yaitu asap cair serbuk kayu karet ( 0%, 5%, 10% dan 15%) dan kayu gelam ( 0%, 5%,10% dan 15%). Parameter yang diamati adalah kadar karet kering (%) dan ketebalan (mm) sit angin yang dihasilkan. Hasil penellitian menunjukkan penambahan asap cair pada perlakuan konsentrasi asap cair kayu karet 10% (K10G0) dapat meningkatkan kadar karet kering dan dapat menghasilkan bokar yang tipis yang ditunjukkan dengan nilai kadar karet kering tertinggi 99,79% dan nilai ketebalan terendah yaitu 2,03 mm.Kata Kunci : kayu karet, kayu gelam, sit angin